The role of neurogenic inflammation in pulp repair and the techniques used for its assessment (narrative review) - Ahmed, Muna Sh.; Mahdee, Anas F. (Frontiers in Dental Medicine, 2025)
Neurogenic inflammation is pivotal in dental pulp repair, involving complex interactions between sensory nerves, immune cells, and dental pulp stem cells (DPSCs). This review aimed to identify the favorable pathways of neurogenic inflammation and neurogenic differentiation of DPSCs in the pulpal healing process. Also, to identify the techniques used to evaluate these inflammatory and differentiation processes. Both PubMed and Google Scholar databases were employed in the search strategy using keyword combinations based on MeSH terms. The search was performed for published articles in English from January 2014 to November 2024, including studies with histological and molecular findings. 29 articles only met the inclusion criteria. Neurogenic inflammation encompasses three main stages: initial (minutes to 24 h), intermediate (24 h to 3 days), and long-term response (3 days to several weeks). The immediate phase includes neuropeptide release, resulting in inflammation and recruitment of immune cells. The intermediate phase features the persistence of neuropeptides, nerve sprouting, and the initiation of repair processes. The long response phase involves resolving inflammation, angiogenesis, decreased neuropeptide levels, and neurogenesis mediated by DPSCs. Advanced methods such as IHC, RNA sequencing, electrophysiological studies, and micro-CT imaging have been employed to evaluate these mechanisms. However, limitations in real-time dynamic assessment highlight the necessity for more advanced and noninvasive procedures for direct evaluation of this complex process.